2017
DOI: 10.18632/oncotarget.16453
|View full text |Cite
|
Sign up to set email alerts
|

Urinary kallikrein 10 predicts the incurability of gastric cancer

Abstract: The current imaging modalities are not sufficient to identify inoperable tumor factors, including distant metastasis and local invasion. Hence, we conducted this study using urine samples to discover non-invasive biomarkers for the incurability of gastric cancer (GC). Urine samples from 111 GC patients were analyzed in this study. The GC cohort was categorized and analyzed according to disease stage and operability. In the discovery phase, protease protein array analysis identified 3 potential candidate protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 46 publications
0
13
0
Order By: Relevance
“…Urine sampling is a straightforward and non-invasive procedure with low risks and costs, representing an attractive option for biomarker detection. We have previously shown the utility of urinary biomarkers for the early detection 10 and prediction of curability 11 against gastric cancer. Urinary biomarker is thus an attractive, non-invasive tool for the detection of malignancies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Urine sampling is a straightforward and non-invasive procedure with low risks and costs, representing an attractive option for biomarker detection. We have previously shown the utility of urinary biomarkers for the early detection 10 and prediction of curability 11 against gastric cancer. Urinary biomarker is thus an attractive, non-invasive tool for the detection of malignancies.…”
Section: Discussionmentioning
confidence: 99%
“…All urine samples were collected before any treatment for CRC, immediately frozen and stored at −80 °C until assayed, as previously reported [10], [11]. Clinical stage was determined by the final pathological diagnosis after resection, according to the 7th edition of the Union for International Cancer Control tumor-node-metastasis classification 14…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Urine and serum samples were collected before any treatment for EC, immediately frozen, and stored at − 80 °C until assayed, as previously reported (16)(17)(18)(19). We obtained EC tissues and matched adjacent normal tissues from patients who underwent surgery or endoscopic submucosal dissection (ESD).…”
Section: Samples and De Nitionmentioning
confidence: 99%
“…However, no urinary biomarkers have been clinically applied to malignant cases. We have been exploring for urinary biomarkers for a long time and found that urinary protein biomarkers are useful for gastric cancer (15)(16)(17) and colorectal cancer (18). Moreover, we recently established a urinary miRNA biomarker panel using miR-6807-5p and miR-6856-5p; this panel can early detect gastric cancer (19).…”
Section: Introductionmentioning
confidence: 99%